The Decision Making of Cryptocurrency Investment in Digital Literacy and Motivation Among Generation Z Through Investment Interest in Indonesia - Retno Purwani Setyaningrum; Wiyatur (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
The growth of cryptocurrency investors in Indonesia has shown a significant increase, especially among Generation Z in 2023. This study focuses on the factors that influence the decision of Generation Z in Indonesia to invest in cryptocurrency. Through a quantitative approach using questionnaires and Structural Equation Modeling (SEM), it was found that digital literacy and investment motivation have a positive effect on cryptocurrency investment decisions. This study, conducted on 160 Generation Z respondents in Indonesia, aims to examine the impact of digital literacy and investment motivation on their interest and decisions in investing in cryptocurrency. The results of this study indicate that digital literacy and investment motivation have a positive influence on Generation Z's cryptocurrency investment decisions. Although investment interest also has a positive effect on cryptocurrency investment decisions, it turns out that digital literacy and investment motivation do not have a significant effect on investment interest. This shows that Generation Z in Indonesia who have high digital literacy and investment motivation will tend to decide to invest in cryptocurrency even though they may not necessarily have an interest in the investment. This finding indicates the need to increase digital literacy and investment motivation in Generation Z so that they can make the right cryptocurrency investment decisions.